Discovery, video self-confrontation, and intervention as a means to improve quality of individual instrumental practice - Brecht-Haddad, Daniel Nagib (Kansas State University, 2017)
The purpose of this research is to discover influences that guide practice habits of collegiate instrumental music students, explore student self-discovery of practice needs, and create strategies that can be used to improve the quality of students’ individual music practice. To best address these intentions, three unique yet sequential studies were implemented. The Discovery study focused on the uncovering prior experiences that shaped students’ practice habits before entering college to get an idea of how current practice habits were formed. The Video Self-Confrontation study had participants watch a video recording of a practice sessions to address possible gaps between their perception and the reality of their practice habits. The video self-confrontation prompted discussion about possibilities for enhanced practice skills. The Intervention study expanded upon information from previous studies to develop and administer personalized interventions designed to address weaknesses and identify effect on participants’ practice habits. Independent practice, the time after instruction when a student works toward mastery of skills or concepts, is widely recognized as a critical component of improvement in the performance music. These studies aim to help bridge the gap between practice theories and optimal experiences. These studies explored elements related to practice behavior. Because each person had unique experiences and diverse ways to describe their experiences, a methodology for each study was required that allowed for structured data collection and organization. As such, the constructivist paradigm supported these studies.
Keywords: Practice; Practice habits; Practice strategies; Deliberate practice; Video self-confrontation